CONGENITAL AND ACQUIRED INTERFERONOPATHIES: DIFFERENTIATED APPROACHES TO THE INTERFERON-CORRECTIVE THERAPY - I. V. Nesterova (LLC "Diagnostics and Vaccines", 2017)
Various disturbances in the interferon system (IFN) - interferonopathy are considered. The classification of developed by the author is given. The clinical features of Type I interferonopathy associated with the overexpression of type I interferons in the rare Mendelian genetic diseases, some autoimmune diseases, the immune dysregulation syndrome, are characterized. The developed methods of targeted therapy of type I interferonopathies aimed at blocking overexpression of type I interferons as hyperproduction IFNa are described. Interferonopathies most often occur as IFN deficiency: congenital or acquired IFNa/b and IFNg deficiencies in children and adults who are associated with atypical viral or mycobacterial infections. Patients with congenital IFNa deficiency are shown to have replacement interferon therapy. With the acquired deficiency of IFNa, differentiated interferon-corrective therapy is performed. For replacement and interferon-corrective therapy, it is used with good clinical efficacy, safe, no side effects, recombinant human IFNa2b in combination with antioxidants - VIFERONR.